Ontology of Mutation Testing for Java Operators (International Journal of Innovative Computing, 2018)
Operators are special characters within the Java language to manipulate primitive data type. Java operators can be classified as unary, binary and ternary. The design of Java operator sometimes becomes confusing when it comes to testing tools as they had the same function with different label in every testing tool.Â  Therefore, in order to map the knowledge of operators correctly, this research has proposed ontology that is dedicated to mutation testing as a means to define the formal specification of concepts and documentation of knowledge of Java operators. Existing papers on ontology did not specify further on entities and properties of operators. Some papers only focus on mutation testing but not the operators. Thus, this paper will present the ontology clearly with the aim to ease end user to identify and understand every classes, properties and relations in Java operators.
Keywords: Mutation testing; ontology; Java operators